Analysis of women participation in farmer group activities in Kwara State, Nigeria - Omotesho Kemi Funmilayo; Akinrinde Adeniyi Felix; Komolafe Sola Emmanuel; Aluko Oyindamola Eunice (Agricultura Tropica et Subtropica, 2019)
The level of access of women to production resources can be enhanced through their active membership and participation in farmers’ associations. However, most farmer-groups in Nigeria are male-dominated. The study therefore analysed women farmers’ participation in farmer-group activities in Kwara State. Specifically, the study identified the expectations of women from group membership; determined their level of participation; identified constraints to participation; and investigated the determinants of participation. A two-stage random sampling technique was used to select 142 women farmers on which a structured interview schedule was administered. Descriptive statistics, Likert scale, and Ordinary Least Square (OLS) Regression Analysis were used to analyse and present the data collected. The results revealed that the mean age, years of experience and farm size of the respondents were 46.9 years, 22 years and 3.2 acres, respectively. Access to farm credit (57 %), self-help (49.4 %), and farm input (31.1 %) were the most important expectations from membership. The level of women participation was low (mean = 2.87) and determined by age, years of experience and farm size at P < 0.05. Financial constraints, poor sense of belonging, inappropriate timing of activities and socio-cultural discrimination were the most severe challenges to participation. The study concluded that women participation in farmer-group activities was low, influenced by their socio-economic characteristics. Therefore, we strongly recommend a multi-dimensional approach to enhance women’s participation in group activities.